2022
DOI: 10.47799/pimr.1002.07
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of coagulase negative staphylococci (CoNS) isolated from various clinical specimens in a tertiary care hospital of southern Rajasthan

Abstract: Background: Coagulase negative staphylococci (CoNS) are a group of staph bacteria, which generally exist as normal flora of human skin and the oral flora found on mucous membranes. CoNS in immunocompromised patients can cause variety of infections like bacteraemia, central nervous system shunt infection, intravascular catheter-related infections, endocarditis, surgical site infections, urinary tract infections, foreign body infection, endophthalmitis, peritonitis and wound, bone and joint infections as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In our study, S. aureus is 100% sensitive to vancomycin, linezolid and teicoplanin such as other studies. [3,9,19] MRSA isolation rate is 15% in our study which is similar to the study of Vijaya and Anuradha [9] (17.66%). Mandira et al [8] and Sharma et al [10] have reported higher MRSA (28.57% and 38.5%), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, S. aureus is 100% sensitive to vancomycin, linezolid and teicoplanin such as other studies. [3,9,19] MRSA isolation rate is 15% in our study which is similar to the study of Vijaya and Anuradha [9] (17.66%). Mandira et al [8] and Sharma et al [10] have reported higher MRSA (28.57% and 38.5%), respectively.…”
Section: Discussionsupporting
confidence: 90%